ANALISIS PERAN KEPEMIMPINAN DEMOKRATIS KEPALA SEKOLAH DALAM MEMBANGUN KOMPETENSI SOSIAL GURU DI SMPK SANTO THOMAS KABUPATEN PAMEKASAN - Anwar, Hairil; Sukarsono, Sukarsono (Jurnal Kebijakan dan Pengembangan Pendidikan, 2018)
Abstract: This study aims to find out 1) the role of the principal's democratic leadership in building the social competence of teachers; 2) know the social competence of teachers. This research was conducted at SMP Thomas Santo Thomas Pamekasan Regency, using a qualitative approach supported by descriptive data. Data analysis is performed by presenting data, data reduction and concluding. The results showed that the role of the democratic leadership of school principals included: 1) As an educator able to facilitate and encourage teachers to improve teacher social competence. 2) As a manager that is facilitating and providing opportunities for teachers to develop their social competence through various education and training activities. 3) An administrator can allocate a budget to improve teacher competencies to build the social competencies of teachers. 4) As a supervisor, namely giving advice and guidance to the teacher's indirect supervision of learning activities in building teacher social competence. 5) As a motivator that is providing educational motivation in carrying out the tasks and functions in building the social competence of teachers. The social competence of teachers is quite good, there is cooperation within the school community which includes the cooperation of fellow teachers, teachers with students, teachers with parents, and teachers with surrounding communities.Keywords: Role of School Principals, Democratic Leadership, Social Competence Abstrak: Penelitian ini bertujuan untuk mengetahui 1) peran kepemimpinan demokratis kepala sekolah dalam membangun kompetensi sosial guru; 2) mengetahui kompetensi sosial guru. Penelitian ini dilaksanakan di SMPK Santo Thomas Kabupaten Pamekasan, dengan menggunakan pendekatan kualitatif didukung data deskriptif. Analisis data dilakukan dengan cara menyajikan data, reduksi data dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa peran kepemimpinan demokratis kepala sekolah antara lain: 1) Sebagai educator mampu memfasilitasi dan mendorong guru dalam meningkatkan kompetensi sosial guru. 2) Sebagai manajer yaitu memfasilitasi dan memberikan kesempatan kepada para guru untuk mengembangkan kompetensi sosialnya melalui berbagai kegiatan pendidikan dan pelatihan. 3) Sebagai administrator yaitu dapat mengalokasikan anggaran untuk peningkatan kompetensi guru sehingga membangun kompetensi sosial para guru. 4) Sebagai supervisor yaitu memberikan saran dan bimbingan kepada guru dalam kegiatan supervisi pembelajaran secara langsung dalam membangun kompetensi sosial guru. 5) Sebagai motivator yaitu memberikan motivasi pendidikan dalam melaksanakan tugas dan fungsinya dalam membangun kompetensi sosial guru. Kompetensi sosial guru yang terjadi cukup baik, adanya kerja sama dalam warga sekolah yang meliputi kerja sama guru sesama guru, guru dengan siswa, guru dengan wali murid, serta guru dengan masyarakat sekitar.Kata kunci: Peran Kepala Sekolah, Kepemimpinan Demokratis, Kompetensi Sosial